2014
DOI: 10.1080/14719037.2014.969762
|View full text |Cite
|
Sign up to set email alerts
|

Information Communication Technology Utilization for Effective Emergency Management Networks

Abstract: Effective communication and coordination are crucial aspects of emergency management. This study examines how organizational representatives perceive information communication technologies (ICTs) in communication and coordination with other organizations. Furthermore, it investigates whether the centrality of organizations in emergency management networks relates to ICT utilization. We found that although many central organizations in emergency preparedness networks have high levels of ICT utilization, ICTs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 55 publications
0
51
0
1
Order By: Relevance
“…For example, IT capabilities are required in knowledge management, change management, inventory management, and so on in the CSC. Similarly, the use of IT in HSC reduces the immediate impact of disaster on society before enhancing the pace of economic recovery and development of a country in the longer term (Díaz Andrade & Urquhart, ; Hu & Kapucu, ). Clemons and Row () and Powell and Dent‐Micallef () argued that in order to realize the benefits of IT, IT should be combined with other factors that produce valuable complementary sustainable resources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, IT capabilities are required in knowledge management, change management, inventory management, and so on in the CSC. Similarly, the use of IT in HSC reduces the immediate impact of disaster on society before enhancing the pace of economic recovery and development of a country in the longer term (Díaz Andrade & Urquhart, ; Hu & Kapucu, ). Clemons and Row () and Powell and Dent‐Micallef () argued that in order to realize the benefits of IT, IT should be combined with other factors that produce valuable complementary sustainable resources.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with first responders, donor agencies, and other officials, disasters become crowded mixes of people, some of whom demonstrate conflicting goals and interests (Tierney and Quarantelli 1989;Tierney et al 2001). Researchers have illustrated several challenges in communicating with and coordinating these multi-actor networks and have recommended the use of information and communication technology to organize activities (Comfort 2005;Kapucu 2006;Hu and Kapucu 2014). However, this research focuses primarily on first responders, other key agencies, and, to a lesser extent, emergent community groups, rather than on individual citizens.…”
Section: From Physical To Online Convergencementioning
confidence: 99%
“…Different types of ICT have been utilized in security networks to help organizations share and process information, establish communication channels, and both reach and engage all necessary stakeholders in order to coordinate collaborative efforts among a large number of actors (Hu & Kapucu, , p. 2). Terrestrial Trunked Radio (TETRA), which was standardized in 1997 by the European Telecommunications Standards Institute (ETSI), is now one of the digital ICTs of choice for many European states.…”
Section: The Management Of Scsmentioning
confidence: 99%
“…Previous research in this area has focused on recent technological advances in communications without investigating either their implementation and management, or the actual abilities and attitudes among end users concerning whether to join a given SCS. In addition, Hu and Kapucu () have revealed that ITCs are often under‐utilized, even by emergency management organizations (p. 19), while Brooks, Bodeau, and Fedorowicz () discovered that many end users have no proper routines for using advanced communications systems in crisis situations even when they possess the proper equipment (Brooks et al, ). The focus of the case study in this article is with the management of a national SCS that was thought to gather all collaborative actors into a single communication system, thus facilitating inter‐organizational and spontaneous communication that arise from each crisis.…”
Section: The Management Of Scsmentioning
confidence: 99%